The superintendent’s role in teacher professional development - Neufeld, Janet K. (Kansas State University, 2016)
School superintendents have traditionally been removed from the systemic process of learning in a school district and instead of been considered more indirect supporters of student achievement. Now, in the face of changing leadership standards, they are being required to provide leadership that more directly enhances student learning by way of teacher professional development. This case study takes a deeper look into the process of the superintendent’s role in district professional development. This will include a purposeful examination to clearly understand the superintendent’s role in designing, implementing, and monitoring professional development in the school district. The study includes (a) the meaning of professional development; (b) examination of school leadership theories and roles; and (c) analysis of how professional development impacts the classroom design of a district instructional framework for professional development.
Keywords: Superintendent; Professional Development; Principals; Teacher Leaders; PSEL; Learning Forward